2017
DOI: 10.1091/mbc.e17-01-0053
|View full text |Cite
|
Sign up to set email alerts
|

Nanonet force microscopy for measuring forces in single smooth muscle cells of the human aorta

Abstract: A number of innovative methods exist to measure cell-matrix adhesive forces, but they have yet to accurately describe and quantify the intricate interplay of a cell and its fibrous extracellular matrix (ECM). In cardiovascular pathologies, such as aortic aneurysm, new knowledge on the involvement of cell-matrix forces could lead to elucidation of disease mechanisms. To better understand this dynamics, we measured primary human aortic single smooth muscle cell (SMC) forces using nanonet force microscopy in both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…-and characterized only biological markers of SMC contractility such as Alpha Smooth Muscle Actin (α-SMA), myosin light chain, or calcium entry and release [20,23,39,46,47]. The only study ever published to our best knowledge on mechanical quantification of contractility in human primary aortic SMCs is by Hall et al [48].…”
Section: Introductionmentioning
confidence: 99%
“…-and characterized only biological markers of SMC contractility such as Alpha Smooth Muscle Actin (α-SMA), myosin light chain, or calcium entry and release [20,23,39,46,47]. The only study ever published to our best knowledge on mechanical quantification of contractility in human primary aortic SMCs is by Hall et al [48].…”
Section: Introductionmentioning
confidence: 99%
“…Cells pull directionally, and these forces are then transmitted back to the substrate by focal adhesions (41). Because cells are able to sense and respond to changes in fiber curvature and structural stiffness (45), deflection of these fibers can be converted to a force measurement (18,42,44,49). Our results showed that, even in the presence of energetic inhibition, the cells were able to sustain a similar amount of force, suggesting that tonic C2C12 force production is a low-energy turnover process, perhaps analogous to the "latch state" observed in other muscle types.…”
Section: Discussionmentioning
confidence: 99%
“…XX) secreting vasoactive agonists, neurotransmitters and GaGs, notably the Heparan Sulfate, which seems to influence the quiescence of the SMCs [91,92]. Further information about this topic can be found in [ [87] or Traction Force Microscopy (TFM) techniques, from common substrate deformation methods [63,76,94] to uncommon specific microdevices [95][96][97]. SMC stiffness is closely linked to their contractile state [84,98].…”
Section: Intracellular Connectionsmentioning
confidence: 99%